Metabolite Profiling of Anti‐Addictive Alkaloids from Four Mexican Tabernaemontana Species and the Entheogenic African Shrub Tabernanthe iboga (Apocynaceae). Issue 4 (12th March 2019) - Krengel, Felix; Chevalier, Quentin; Dickinson, Jonathan; Herrera Santoyo, Josefina; Reyes Chilpa, Ricardo
Abstract: Ibogaine and other ibogan type alkaloids present anti‐addictive effects against several drugs of abuse and occur in different species of the Apocynaceae family. In this work, we used gas chromatography‐mass spectrometry (GC/MS) and principal component analysis (PCA) in order to compare the alkaloid profiles of the root and stem barks of four Mexican Tabernaemontana species with the root bark of the entheogenic African shrub Tabernanthe iboga . PCA demonstrated that separation between species could be attributed to quantitative differences of the major alkaloids, coronaridine, ibogamine, voacangine, and ibogaine. While T. iboga mainly presented high concentrations of ibogaine, Tabernaemontana samples either showed a predominance of voacangine and ibogaine, or coronaridine and ibogamine, respectively. The results illustrate the phytochemical proximity between both genera and confirm previous suggestions that Mexican Tabernaemontana species are viable sources of anti‐addictive compounds. Abstract :